Mă poate ajuta cineva?
Anexe:
Răspunsuri la întrebare
Răspuns de
5
4√3(2√75-√27+3√12)-2√3·√48=4√3(2√3·25-√3·9+3√3·4)-2√3·√3·16=
=4√3(2·5√3-3√3+3·2√3)-2·4√3·√3=4√3(10√3-3√3+6√3)-2·4·3=
=4√3·13√3-2·4·3=52·3-24=156-24=132
(√243-2√3)·(√147)+3√8·(5√72)+6√128=
(√3·81-2√3)·(√3·49)+3(√2·4)·(5√2·36)+6√2·64=
(9√3-2√3)(7√3)+6√2(30√2)+48√2=
7√3·(7√3)+180·2+48√2=49·3+360+48√2=147+360+48√2=507+48√2
=4√3(2·5√3-3√3+3·2√3)-2·4√3·√3=4√3(10√3-3√3+6√3)-2·4·3=
=4√3·13√3-2·4·3=52·3-24=156-24=132
(√243-2√3)·(√147)+3√8·(5√72)+6√128=
(√3·81-2√3)·(√3·49)+3(√2·4)·(5√2·36)+6√2·64=
(9√3-2√3)(7√3)+6√2(30√2)+48√2=
7√3·(7√3)+180·2+48√2=49·3+360+48√2=147+360+48√2=507+48√2
StefiSteff:
Mersi !
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă